Ethnicity, Religion and The Changing Community Structure Within Fakfak Society in Papua - Ade Yamin; Musa Rumbaru; Nining Lestari; Mufliha Wijayati (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
Through in-depth research using an ethnographic method, this article seeks to show what changes are taking place in the Fakfak community regarding culture, religion, and composition. This research aims to fill the research gap from previous studies by looking at how religion has rapidly changed the structure of society (both in terms of identity and population demographics) even though they come from the same kinship in a nuclear family. This article found that religion has become society’s primary agent of change, with positive and negative connotations. However, at the same time, the community has a local knowledge called “toromit wat istery” which is used as an unbreakable bond due to clashes between religions. This unity in diversity is a fundamental value that the community must observe. As an implication, these changes in the Fakfak community serve as an example of the resilience of local values in the face of the clash of global values that must be protected and maintained as the primary source of national resilience.